2008
DOI: 10.2337/dc08-1013
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Cardiovascular Events in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -The purpose of this study was to assess incidence of and risk factors for recurrent cardiovascular disease (CVD) in type 2 diabetes.RESEARCH DESIGN AND METHODS -We estimated the incidence of recurrent cardiovascular events in type 2 diabetic patients, aged 40 -97 years, followed by a network of diabetes clinics. The analysis was conducted separately for 2,788 patients with CVD at enrollment (cohort A) and for 844 patients developing the first episode during the observation period (cohort B).RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 29 publications
6
33
0
3
Order By: Relevance
“…5 The effects of RHL on hepatic morphology and fat accumulation. The mice were anesthetized with chloral hydrate, and the liver tissue was removed and fixed in 10 % neutral buffered formalin, embedded in paraffin, sectioned with 5 lm thickness, and then stained with hematoxylin-eosin (a) or with Nile red (b) 285 million people who had diabetes and it is estimated this number will be double by 2030 (Wild et al 2004;Herman 2007;Giorda et al 2008). However, hypoglycemic agents on the market can not effectively control blood glucose and prevent the occurrence of complication.…”
Section: Discussionmentioning
confidence: 99%
“…5 The effects of RHL on hepatic morphology and fat accumulation. The mice were anesthetized with chloral hydrate, and the liver tissue was removed and fixed in 10 % neutral buffered formalin, embedded in paraffin, sectioned with 5 lm thickness, and then stained with hematoxylin-eosin (a) or with Nile red (b) 285 million people who had diabetes and it is estimated this number will be double by 2030 (Wild et al 2004;Herman 2007;Giorda et al 2008). However, hypoglycemic agents on the market can not effectively control blood glucose and prevent the occurrence of complication.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Hence, identification of markers of increased risk for development of cardiovascular disease (CVD), that add to established risk parameters for CVD such as smoking, 4 cholesterol level, 5 albuminuria 6,7 and creatinine level, 8 is important.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of United Kingdom Prospective Diabetes Study (UKPDS) data found a 2% per annum progression from normo-to micro-albuminuria, as well as an additional 2% per annum progression from microalbuminuria to proteinuria [13]. An Italian study of the recurrence of cardiovascular events in people with type 2 diabetes reported a 72.7 per 1000 patient-years incidence of a recurrent event in men with cardiovascular disease at time of enrolment and a 32.5 incidence in women [14].Over the last decade, there has been a rapid escalation in the prevalence of obesity, one that parallels the equally rapid increase in type 2 diabetes [15]. The World Health Organization (WHO) considers obesity to be a global epidemic [16].…”
mentioning
confidence: 99%